Musculoskeletal modelling of handcycling motion on an erogometer: influence of crank position on training purposes - Wolbert, F. A.J.; Peters, M.; Viellehner, J.; Funken, J.; Potthast, W. (ISBS Proceedings Archive (Michigan), 2017)
The objective of this study was to examine the influence of crank position during hand cycling on muscle forces and Glenohumeral joint reaction forces. Twelve male subjects performed 16 trials with variation in crank parameters. 3D motion capturing (Vicon) and custom made handlebars (Kistler force sensors) were used to determine kinematic and kinetic data. Musculoskeletal modelling (AnyBody) was used for calculations of joint contact and muscle forces. Significant difference was found between settings and muscle forces (p=0.006) and Glenohumeral joint reaction forces (p=0.000). For the m. Brachialis, the m. Latissimus Dorsi and the m. Deltoideus Scapularis, an optimal setting was found. The antero- posterior and distraction force are minimized with horizontal handlebars, a small crank width and long crank arms